IMMUNOGYSTOCHEMICAL ASSESSMENT OF THE EXPRESSION OF KI-67 AND P53 MARKERS IN PEDIATRIC NEPHROPLASTOMA - Sarvar T. Islamov; Mirza-Ali A. Gafur-Akhunov; Khasan Z. Tursunov; Alisher B. Yigitaliyev (Central Asian Journal of Medicine, 2025)
In this study, the levels of expression of immunohistochemical markers Ki-67 and p53 in various morphological variants of nephroblastoma (Wilms tumor) in children were studied. The study was conducted in 2020-2024 with the participation of 60 patients with nephroblastoma who were treated in specialized medical institutions of the city of Tashkent. Of these, 20 had epithelial, 20 had mesenchymal, and 20 had mixed forms of nephroblastoma. The Ki-67 marker was evaluated as a protein controlling the proliferative activity of tumor cells, and p53 as a protein controlling the processes of damage and apoptosis in the genome. According to the obtained results, a high degree of positive reactions prevailed in all variants. In particular, in the epithelial type, high expression was observed in 60% of cases for Ki-67 and in 40% of cases for p53. High proliferative and genetic activity was also noted in mesenchymal and mixed species. These indicators confirm the significance of immunohistochemical markers in assessing the aggressive course and prognosis of nephroblastoma.